Feline osteochondromatosis in a FELV-negative European shorthair cat - Nolff, M. C.; Puff, C.; Länger, B.; Fehr, M. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2014)
Objective: To report palliative treatment in a case of multifocal feline osteochondromatosis in a feline leukaemia virus (FeLV) negative European shorthair cat. Case: A 6-year-old spayed female European shorthair cat was presented because of a right forelimb lameness caused by an osteochondromatous lesion which had trapped tendons, vessels and nerves of the antebrachium. Several other lesions were present which did not cause the animal discomfort. The cat was tested negative for FeLV. Palliative surgical removal of the mass was performed, resulting in a marked improvement of mobility with no local recurrence. The cat developed a non-regenerative anaemia after surgery, however the underlying cause was not identified upon request of the owner. Overall survival after surgery was only 2 months. The cat was then euthanised due to severe progression of the anaemia. Conclusion: Palliative surgical removal of osteochondromas may result in local improvement. However, owners need to be aware that it does not increase overall survival and that the prognosis is poor. Infection with FeLV is not necessarily associated with such lesions.
Keywords: Feline osteochondromatosis; cat; palliative treatment; osteocartilaginous lesion; FELV infection